MOBILISATION OF TRAFFIC-DERIVED TRACE METALS FROM ROAD CORRIDORS INTO COASTAL STREAM AND ESTUARINE SEDIMENTS, CAIRNS, NORTHERN AUSTRALIA - Pratt C.; Lottermoser B.G. (My University, 2007)
This investigation revealed the presence of traffic-derived metals within road, stream and estuarine sediments collected from a coastal catchment, northern Australia. Studied road sediments displayed variable total metal concentrations (median Cd, Cu, Pb, Pd, Pt, Ni and Zn values: 0.19, 42.6, 67.5, 0.064, 0.104, 36.7 and 698 mg/kg, respectively). The distinctly elevated Zn values are due to abundant tyre rubber shreds (as verified by SEM-EDS and correlation analysis). By comparison to the road sediments, background stream sediments taken upstream from roads have relatively low median Pb, Pd, Pt and Zn concentrations (7.3 mg/kg Pb, 0.01 mg/kg Pd, 0.012 mg/kg Pt, 62 mg/kg Zn). Stream and estuarine sediment samples collected below roads have median values of 21.8 mg/kg Pb, 0.014 mg/kg Pd, 0.021 mg/kg Pt and 71 mg/kg Zn, and exhibit 207Pb/206Pb and 208Pb/206Pb ratios that appear on a mixing line between the isotopically distinct background stream sediments and the road sediments. Thus, mobilisation of dusts and sediments from road surfaces has resulted in relatively elevated Pb, Pd, Pt and Zn concentrations and non-radiogenic Pb isotope ratios in local coastal stream and estuarine sediments. The investigation demonstrates that traffic-derived metals enter coastal stream and estuary sediments at the fringe of the Great Barrier Reef lagoon.
Keywords: TRAFFIC POLLUTION; ROAD SEDIMENTS; STREAM SEDIMENTS; METALS; PB ISOTOPES; AUSTRALIA